2012
DOI: 10.1128/ec.00222-12
|View full text |Cite
|
Sign up to set email alerts
|

VeA Regulates Conidiation, Gliotoxin Production, and Protease Activity in the Opportunistic Human Pathogen Aspergillus fumigatus

Abstract: bInvasive aspergillosis by Aspergillus fumigatus is a leading cause of infection-related mortality in immunocompromised patients. In this study, we show that veA, a major conserved regulatory gene that is unique to fungi, is necessary for normal morphogenesis in this medically relevant fungus. Although deletion of veA results in a strain with reduced conidiation, overexpression of this gene further reduced conidial production, indicating that veA has a major role as a regulator of development in A. fumigatus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 99 publications
(170 reference statements)
6
72
0
Order By: Relevance
“…Herein, A. niger exposed to GT led to an increase abundance in AglB, LacA and AglA, which are under the control of XlnR. In A. fumigatus, deletion of veA was shown to cause a reduction of protease activity [60]. We conclude that it is possible that the changes observed in the production of hydrolytic enzymes, after GT addition, are mediated by alterations to the Velvet complex.…”
Section: Discussionmentioning
confidence: 74%
“…Herein, A. niger exposed to GT led to an increase abundance in AglB, LacA and AglA, which are under the control of XlnR. In A. fumigatus, deletion of veA was shown to cause a reduction of protease activity [60]. We conclude that it is possible that the changes observed in the production of hydrolytic enzymes, after GT addition, are mediated by alterations to the Velvet complex.…”
Section: Discussionmentioning
confidence: 74%
“…A well studied example is A. fumigatus gliotoxin which is known to induce apoptosis and prevents NF-kB activation by inhibition of the proteasome and suppression of angiogenesis. [27][28][29][30][31] Additionally, fumagillin is also produced by A. fumigatus during hyphal growth and has been identified as an inhibitor of angiogenesis through a covalent interaction with methionine aminopeptidase-2 and suppresses tumor growth. 32,33 The production of gliotoxin and fumagillin was also proved in infected G. mellonella larvae.…”
Section: Discussionmentioning
confidence: 99%
“…At 37 C, all larvae infected with 1 £ 10 7 conidia died within 72 h, while survival still reached 70% in those incubated at 30 C and it took 6 days before all larvae died. Infection with 1 £ 10 6 conidia at 37 C resulted in 100% mortality at day 6, while almost 50% survival was monitored at 30 C. Lower inoculum density (1 £ 10 5 ) resulted in 50% mortality at day 6 at 37 C, whereas larvae kept at 30 C survived the infection (less than 10% mortality). Heat-inactivated conidia of T90 were not able to cause mortality and survival was more than 80% after 120 h incubation at either 30 C or 37 C (data not shown).…”
Section: Killing Of Galleria Mellonella Larvae By a Terreus Isolatesmentioning
confidence: 99%
“…In spite of these new findings, only a few metabolites have been associated with these clusters (16), among them the clusters associated with the synthesis of kojic acid, as well as the synthesis of AFs, CPA, aflatrem, and asparasone. Expression of these last four gene clusters was shown to be dependent on the global regulatory gene veA, which is also involved in developmental regulation in A. flavus (17)(18)(19)(20) and in other fungi (21)(22)(23)(24)(25)(26). Previous studies, conducted mainly with the model fungus Aspergillus nidulans, revealed that the VeA protein forms a complex with LaeA, a chromatin-modifying protein, and the regulator VelB, another protein of the velvet family.…”
mentioning
confidence: 99%